A computer vision-based alarming system for real-time detection of driver sleep - Khalifa, Othman Omran; Mohd Ariffian amnah, Shera Shahida (2014)
Driver’s alertness on road is very important in order to avoid any misfortunate accidents that can lead to injuries and in some worst case, death. The statistics proves that one of the significant factors that cause car crash is the driver sleepiness. In order to prevent any future accidents and as well as to prevent the driver from falling asleep during driving, this project is proposed. In this project, a proposed computer vision-based alarming system for real-time of driver sleep is presented. The system is suitable for driver monitoring as it does not disturb the driver with his driving. The proposed system involves the detection of the face of the driver with the help of a camera. Then, the facial features extraction is done for further processing. After that, the driver’s eye state whether it is open or closed is then determined. If the eyes of the driver are closed for some particular time, a warning is issued and thus generates the alarm